Ground spider assemblages (Araneae: Gnaphosidae) along an urban-rural gradient in the city of Heraklion, Greece - Dimitris KALTSAS (European Journal of Entomology, 2014)
The responses of gnaphosid spiders to an urbanization gradient (urban-suburban-rural areas) were studied using pitfall traps in and near the city of Heraklion, in Crete, Greece, from October 2010 to October 2011. Our results indicate that richness and abundance of species of spiders decreased from the rural area to the center of the city, but not significantly so. Temporal beta diversity was significantly higher in urban areas, which indicates a high temporal variability in species composition of gnaphosid assemblages in the center of the city that takes the form of complementary rather than synchronized phenologies of co-occurring species, as expected in habitats degraded by high levels of disturbance. There was no specific pattern in the body size distribution of the gnaphosids along the urban-rural gradient, and thus the decrease in mean body size with increase in urbanization hypothesis was not supported by our results. However, the species composition recorded in urban areas was very different from that in suburban and rural areas. The percentage of individuals in the catches that were generalist species differed significantly along the gradient. As generalist gnaphosid species made up 72.01% of the total caught in the center of the city, and only 9.53% and 2.07% in suburban and rural areas respectively, our results support the opportunistic species hypothesis. Our analyses indicate that Urozelotes rusticus, a well known synanthropic species recorded for the first time in Greece, is an indicator of high levels of urbanization in Heraklion.